Impact of natural disaster on public sector corruption - Eiji Yamamura (Institute for Advanced Development Studies (INESAD), 2013)
This paper uses inter-country panel data obtained during the period 1990-2010 to examine how the occurrence of natural disasters has affected corruption within the public sector. There are a number of new findings from this study. (1) Disaster with the large amount of damage increase corruption not only for developing countries but also for developed countries. (2) The effect of disasters is greater in developed countries than in developing countries. (3) In the developed countries, frequency of occurrence of disaster plays important role on increasing corruption. This suggests that foreseeable disasters increase corruption. In developed countries, people have an incentive to live within disaster-prone areas to seek compensation.
Keywords: D73; D81; Q54; 330; Corruption; Institution; Disasters; Risk